Membranoproliferative glomerulonephritis following tubulointerstitial nephritis is a late manifestation of IgG4-related kidney disease: A distinctive case - Joichi Usui; Steven P. Salvatore; Mourhege Alsaloum; Alla Goldberg; Sheng Kuo; Surya V. Seshan (Elsevier, 2019)
IgG4-related kidney disease (IgG4RKD) generally presents as an active and chronic fibrosing tubulointerstitial nephritis. Recent reports have described glomerular lesions, typically with IgG4 containing subepithelial/membranous deposits as part of IgG4RKD. Herein, we report a case of IgG4-related membranoproliferative glomerulonephritis and associated tubulointerstitial nephritis in the clinical setting of IgG4-related autoimmune disease. A 75-year-old male diabetic patient with renal dysfunction showed IgG4-related tubulointersitital nephritis (TIN) superimposed on mild diabetic nephropathy by renal biopsy and was on 2 months of steroid therapy. Three years later, he developed progressive renal failure and heavy proteinuria leading to a second biopsy which showed, IgG4-dominant membranoproliferative pattern of glomerulonephritis (MPGN) along with chronic fibrosing IgG4-related tubulointerstitial disease. The development of MPGN is a rare lesion in association with IgG4 related TIN and may represent a late manifestation of IgG4RKD or continued complement activation. Keywords: Membranoproliferative glomerulonephritis, IgG4-related kidney disease, Tubulointerstitial nephritis, Diabetic nephropathy